From Meso to Macro: Controlling Hierarchical Porosity in Supraparticle Powders - Sultan, Umair; Götz, Alexander; Schlumberger, Carola; Drobek, Dominik; Bleyer, Gudrun; Walter, Teresa; Loewer, Erik; Peuker, Urs Alexander; Thommes, Matthias; Spiecker, Erdmann; Apeleo Zubiri, Benjamin; Inayat, Alexandra; et al. (Small, 2023)
A drying droplet containing colloidal particles can consolidate into a spherical assembly called a supraparticle. Such supraparticles are inherently porous due to the spaces between the constituent primary particles. Here, the emergent, hierarchical porosity in spray-dried supraparticles is tailored via three distinct strategies acting at different length scales. First, mesopores (<10 nm) are introduced via the primary particles. Second, the interstitial pores are tuned from the meso- (35 nm) to the macro scale (250 nm) by controlling the primary particle size. Third, defined macropores (>100 nm) are introduced via templating polymer particles, which can be selectively removed by calcination. Combining all three strategies creates hierarchical supraparticles with fully tailored pore size distributions. Moreover, another level of the hierarchy is added by fabricating supra-supraparticles, using the supraparticles themselves as building blocks, which provide additional pores with micrometer dimensions. The interconnectivity of the pore networks within all supraparticle types is investigated via detailed textural and tomographic analysis. This work provides a versatile toolbox for designing porous materials with precisely tunable, hierarchical porosity from the meso- (3 nm) to the macroscale (≈10 µm) that can be utilized for applications in catalysis, chromatography, or adsorption.
CRIS-Team Scopus Importer:2023-04-07
Keywords: adsorption; hierarchy; porous materials; self-assembly; supraparticles; tomography